ANTIOXIDANT ACTIVITY of THE SECONDARY METABOLITES PRODUCED by ENDOPHYTIC FUNGI ISOLATED from JERUJU (Acanthus ilicifolius L.) PLANT - Putri, Amanda Rahmaniah; Salni, Salni; Widjajanti, Harry (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2019)
Twelve endophytic fungi were isolated from Jeruju plant. Three of which have the best antioxidant activity, namely Culvularia lunata DJS1, Diaporthe phaseolorum DJS2, and Colletotrichum siamense BJS4. The fungi can produce secondary metabolites that have the potential as antioxidant compounds. This study aims to isolate the antioxidant compound using a chromatography column and test the antioxidant activity using DPPH method. Isolation of secondary metabolites produced 40 eluates. The IC50 value of DJS111 and BJS42 eluates were 10.20 µg/ml and 20.89 µg/ml, which is an antioxidant compound with very strong activity. The IC50 value of DJS24 eluate was 54.45 µg/ml, which is strong antioxidant activity. DJS111 eluate has antioxidant activity that approaches to ascorbic acid as a standart antioxidant compound (7.76µg/ml). From TLC, DJS111 contains flavonoid compound and DJS24 and BJS42 contain terpenoid compound.